Spiritual management of natural resources for climate smart agriculture, global food and livelihood security - Singh, Satyendra Kumar (Indian Farming, 2020)
Today India is facing a great challenge of degraded natural resources like soil, water, plants, and air. Because of intensive agricultural practices, farmers are using indiscriminate doses of chemical fertilizers and pesticides due to ignorance and greed. This results in soil erosion, soil acidification, loss of soil microbial activities and great increase in pollution level leading to floods, famines and droughts etc. along with poor soil health and fertility. In the light of these facts and figures, one can easily conclude that the real problems today are not economic and political but organic, spiritual and moral. Hence, the lasting and eternal solutions to these problems can be found only in Spiritual Natural Sustainable Organic Farming System.